2012
DOI: 10.2133/dmpk.dmpk-11-rg-077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nuclear Receptor Downregulation on Hepatic Expression of Cytochrome P450 and Transporters in Chronic Hepatitis C in Association with Fibrosis Development

Abstract: Analysis of mRNAs from liver biopsy samples of patients with chronic hepatitis C revealed that the levels of nuclear receptor expression were correlated with those of drug-metabolizing enzymes and transporters in relation to the development of fibrosis. Overall, the median mRNA level was largely dependent on fibrosis stage (F), and that for stage 3 patients (F3) was about 50% less than that for F1 patients. Levels of expression of AhR, together with CAR and PXR, were lowest in livers of F3 patients. Multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 19 publications
1
51
0
4
Order By: Relevance
“…Relative mRNA expression of OATP1B1 and OATP2B1 was reduced in the livers of patients with chronic HCV infection, although the mechanistic link between inflammatory cytokines and OATP downregulation is not clear. 108,109 Downregulation of NTCP, OAT2, and OCT1 correlated with fibrosis state, but another study observed no difference compared to control samples. 108,109 In the presence of HCV-induced cirrhosis, expression of NTCP, OATP1B3, and OCT1 are decreased compared to control samples using proteomic analysis.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Relative mRNA expression of OATP1B1 and OATP2B1 was reduced in the livers of patients with chronic HCV infection, although the mechanistic link between inflammatory cytokines and OATP downregulation is not clear. 108,109 Downregulation of NTCP, OAT2, and OCT1 correlated with fibrosis state, but another study observed no difference compared to control samples. 108,109 In the presence of HCV-induced cirrhosis, expression of NTCP, OATP1B3, and OCT1 are decreased compared to control samples using proteomic analysis.…”
Section: Introductionmentioning
confidence: 95%
“…108,109 Downregulation of NTCP, OAT2, and OCT1 correlated with fibrosis state, but another study observed no difference compared to control samples. 108,109 In the presence of HCV-induced cirrhosis, expression of NTCP, OATP1B3, and OCT1 are decreased compared to control samples using proteomic analysis. 110 …”
Section: Introductionmentioning
confidence: 95%
“…Interestingly, a multivariate linear regression analysis revealed that AhR (and PXR) expression might be involved in SLC22A1 gene expression in the livers of patients with chronic hepatitis C. Nevertheless, no direct data indicate the induction of hepatic SLC22A1 gene expression by AhR ligands (Hanada et al, 2012).…”
Section: Ligand-dependent Nuclear Receptor-mediated Regulationmentioning
confidence: 99%
“…It is reported that the CYP 1A subgroup (a specific isoforms of P450) is significantly reduced in three experimental models of hepatic fibrosis when there is evidence of increased collagen deposition in the livers (Peterson et al, 2000). Not only that, but the expressions of many enzymes and transporters which are related to the internal metabolism and transportation of drugs have remarkably down regulated during the progression of liver fibrosis (Hanada et al, 2012). So, liver fibrosis leading to the change of protein expression and/or activity of most drugs metabolizing enzymes, may have complex effects on drug clearance, biotransformation, pharmacokinetics and tissue distribution.…”
Section: Introductionmentioning
confidence: 99%